2020
DOI: 10.1002/adma.202002575
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Nonreciprocal Circularly Polarized Emission from an Organic Thin Film

Abstract: Controlling circularly polarized (CP) emission is key for both fundamental understanding and applications in the field of chiral photonics and electronics. Here, a completely new way to achieve this goal is presented. A luminescent thin film, made from a chiral conjugated phenylene bis‐thiophenylpropynone able to self‐assemble into ordered structures, emits highly circularly polarized light with opposite handedness from its two opposite faces. Such emergent nonreciprocal behavior in CP emission, so far unprece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
88
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 35 publications
4
88
0
1
Order By: Relevance
“…A further source of artifacts is due to photoselection, which is strictly related to the experiment geometry and to the polarization of the exciting radiation [5] . More recently, evidence of the interference between luminescence anisotropy and linear birefringence has been reported, which leads to CPL with the observation of non‐reciprocal CPL [6] …”
Section: Figurementioning
confidence: 97%
See 2 more Smart Citations
“…A further source of artifacts is due to photoselection, which is strictly related to the experiment geometry and to the polarization of the exciting radiation [5] . More recently, evidence of the interference between luminescence anisotropy and linear birefringence has been reported, which leads to CPL with the observation of non‐reciprocal CPL [6] …”
Section: Figurementioning
confidence: 97%
“…[5] More recently,e videnceo ft he interference between luminescence anisotropy and linear birefringence hasb een reported,w hich leads to CPL with the observation of non-reciprocal CPL. [6] In recent years CPL hasf ound appealinga pplicationsi no rganic optoelectronics and photonics. [7] In order to obtain circularly polarized electroluminescence (CPEL), the final emitter must be chiral and non-racemic, which can be obtained with several strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In such systems, the excitation of donors that incorporate heavy atoms permits intersystem crossing to triplet states, and their chirality results in the generation of spin‐polarised triplet excitons which ultimately enhance the g PL of chiral acceptors [18] . For small molecules which self‐assemble into anisotropic aggregates, Zinna, Di Bari and co‐workers have shown it is possible to achieve high | g PL | (10 −2 ) through a coupling of linear fluorescence anisotropy and linear birefringence [20] . Alternatively, efforts have been made to induce chiroptical effects into otherwise achiral molecules, primarily through the incorporation of carefully selected achiral molecules into chiral media.…”
Section: Figurementioning
confidence: 99%
“…[18] For small molecules which self-assemble into anisotropic aggregates, Zinna, Di Bari and co-workers have shown it is possible to achieve high j g PL j (10 À2 ) through a coupling of linear fluorescence anisotropy and linear birefringence. [20] Alternatively, efforts have been made to induce chiroptical effects into otherwise achiral molecules, primarily through the incorporation of carefully selected achiral molecules into chiral media. For example, Zhu, Liu et al demonstrated the induction of CPL (j g PL j % 10 À2 ) of achiral small molecule luminophores when embedded within the chiral voids of a cubic, self-assembled cyclodextrin metal organic framework.…”
mentioning
confidence: 99%